Navigating Challenges for Sustainable Growth Insights from the Indian G20 Presidency - Bery, Suman; Kapoor, Kapil; Arcand, Jean-Louis.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
The open access volume stems from a conference held during the Indian G20 Presidency in New Delhi on 28-29 July 2023, featuring 40 leading experts from 14 countries across the world. It addresses issues, such as climate adaptation, global health, technology, and financial investments. It discusses India's transition to net-zero emissions, the dynamics of technological disruptions, the shift towards a unified digital economy, and the transformations in the global economy. It critically analyzes the global financial architecture, the evolving nature of capital and the job market, and the complex interplay between economics, politics, and global health. It also discusses the uneven progress in international development, focusing on Africa's unique challenges and potentials. With expert contributions across sectors, including policy, academia, and industry, the volume provides cross-cutting insights that resonate with multiple stakeholders and offer pragmatic agendas for a sustainable future. This book stands as a crucial resource for anyone keen on understanding or influencing sustainable growth on a global scale.
Foreword -- Preface -- Executive Summary -- Session 1: Energy, Climate, Growth -- Chair: Jayant Sinha -- Speakers: Jessica Seddon, Robert Stavins, Arunabha Ghosh -- Session 2: Technology, Policy, Jobs -- Chair: Sachin Chaturvedi -- Speakers: Paul Samson, Albert van Jaarsveld, Debjani Ghosh -- Expert Comment: Vijay Kumar Saraswat -- Session 3: Growth Implications of a Fractured Trading System -- Chair: Peter Drysdale -- Speakers: Alicia Garcia-Herrero, Nagesh Kumar, Otaviano Canuto -- Expert Comment: B.V.R. Subrahmanyam -- Session 4: Reshaping Global Finance for Sustainable Growth -- Chair: N. K. Singh -- Speakers: Hanan Morsy, Tao Zhang, Poonam Gupta -- Expert Comment: Manjeev Singh Puri -- Virtual Discussion and Wrap Up of Day 1 -- Topics: Technology, Policy, Jobs; Multilateralism: Geopolitics, Governance and the Global Commons -- Speakers: Robert Lawrence, Homi Kharas -- Session 5: Multilateralism: Geopolitics, Governance and the Global Commons -- Chair: V. Anantha Nageswaran -- Speakers: Jean-Louis Arcand, Mari Pangestu, Ram Madhav -- Expert Comment: Ramesh Chand -- Session 6: Adjustment, Resilience and Inclusion in an Uncertain World -- Chair: François Bourguignon -- Speakers: Santiago Levy, Haroon Bhorat, Surjit Bhalla -- Expert Comment: Vinod Kumar Paul -- Keynote Address by Nandan Nilekani -- Appendices -- Conference Outline -- About the Organisers -- Acknowledgements -- About the Speakers.
Keywords: Environmental sciences -- Social aspects; Sustainability; Economic geography; Environmental Social Sciences; Sustainability; Economic Geography